The Rate of Influenza Vaccination after Face-to-Face Interview in Pregnancy - Orgul, Gokcen; Keles, Ayse Istek; Yucel, Aykan; Sahin, Dilek (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Purpose Most societies recommend routine influenza vaccine to all pregnant women. In Turkey, the Ministry of Health provides the influenza vaccine free of charge to pregnant women during the second and third trimesters. Pregnant women may not be willing to accept vaccination despite their knowledge and attitudes. We aimed to investigate the rate and determining factors of influenza vaccine acceptance after receipt of face-to-face information.Methods Pregnant women were informed about the benefits of the influenza vaccine and asked if they would get the vaccine.Results A total of 353 Turkish women were involved, and 191 (54.1%) accepted influenza vaccination. There was no statistically significant difference in terms of maternal age, body mass index, gravida, number of children, socioeconomic status, smoking and occupation between groups. Women in the third trimester had lower vaccination rates compared to first- and second-trimester pregnancies (35.7% vs. 67.7–64.2%). Women with at least a university degree also had lower vaccine uptake rates (58.1% vs. 59.5–36.8%). While 82.2% of women who accepted vaccination believed the benefit of the vaccine to the baby, the rate was 54.9% in the non-vaccinated group. The most common reason for refusal was the belief that influenza was not a serious disease. Vaccination uptake was higher especially for women who understood the benefits of the influenza vaccine for the baby (OR=3.79, 95%Cl=2.34–6.14).Conclusion Women who had enough information, who had a lower education level, who had a previous history of influenza infection, and who had decided to have their babies vaccinated were more likely to accept influenza vaccine.
Keywords: Influenza A (H1N1); vaccination; pregnancy; Turkey